1989
DOI: 10.1007/bf00265403
|View full text |Cite
|
Sign up to set email alerts
|

The genetic predisposition to fibrocalculous pancreatic diabetes

Abstract: Summary. Fibrocalculous pancreatic diabetes (previously known as tropical pancreatic diabetes) is a rare cause of diabetes confined to countries within the tropical belt. The aetiology of fibrocalculous pancreatic diabetes is thought to be environmental although the agent(s) is unknown. We have investigated a possible genetic basis of this disease by looking for restriction fragment length polymorphisms of genes implicated in the aetiology of diabetes rnellitus. Seventy-six Dravidian patients with fibrocalculo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
4
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 43 publications
1
25
4
1
Order By: Relevance
“…We were unable to support our previous observation in south Indians of an association between FCPD and the insulin gene locus. 6 The HLA-DQB1 association found in this study is different to that found in eastern and south Indian populations. 6,8,9 The most marked difference is the non-transmission of HLA-DQ2, indicating that this allele protects from FCPD, in contrast to T1DM in which it is positively associated in many ethnic groups, including subjects from the Indian sub-continent.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…We were unable to support our previous observation in south Indians of an association between FCPD and the insulin gene locus. 6 The HLA-DQB1 association found in this study is different to that found in eastern and south Indian populations. 6,8,9 The most marked difference is the non-transmission of HLA-DQ2, indicating that this allele protects from FCPD, in contrast to T1DM in which it is positively associated in many ethnic groups, including subjects from the Indian sub-continent.…”
Section: Discussioncontrasting
confidence: 99%
“…6 The HLA-DQB1 association found in this study is different to that found in eastern and south Indian populations. 6,8,9 The most marked difference is the non-transmission of HLA-DQ2, indicating that this allele protects from FCPD, in contrast to T1DM in which it is positively associated in many ethnic groups, including subjects from the Indian sub-continent. 8,11 Furthermore three FCPD patients in this study were positive for the HLA-DQB1*0602 allele; this underlines the difference between genetic susceptibility to FCPD and T1DM, as the HLA-DQB1*0602 allele is extremely rare in cases of T1DM.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…2 Furthermore, whereas an association between the insulin gene hypervariable region and T1DM has been found in most ethnic groups, this has not been found in South Indian subjects. 1,3 It is therefore conceivable that individuals with T1DM in South India might have input from a greater range of different susceptibility loci compared to other ethnic groups.…”
Section: Introductionmentioning
confidence: 99%